2003
DOI: 10.1080/15140326.2003.12040592
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Order of Integration with Low Power Tests. an Application to Argentine Macro-Variables

Abstract: The low power of available econometric tests is an important problem in applied research on unit roots and related issues. Based on the principle of methodological triangulation, the problem should be analyzed from different points of view in order to increase the validity of the results. Following this approach a strategy to test the order of integration in time series is presented using a sequence of eleven consolidated tests. In this way it is possible to determine the persistence of shocks, to specify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…So, shocks are more important and less symmetric for Mercosur countries. In spite of this, many authors (Licandro Ferrando, 2000;Carrera et al, 1998) have found that shocks became more symmetric during the last years, as the integration process went on.…”
Section: B How Asymmetric Are Shocks To Mercosur Countries?mentioning
confidence: 99%
See 1 more Smart Citation
“…So, shocks are more important and less symmetric for Mercosur countries. In spite of this, many authors (Licandro Ferrando, 2000;Carrera et al, 1998) have found that shocks became more symmetric during the last years, as the integration process went on.…”
Section: B How Asymmetric Are Shocks To Mercosur Countries?mentioning
confidence: 99%
“…For an analysis of trade specialisation and the relationship between the two major partners in the block, Argentina and Brazil, see Miotti,Quenan and Winograd (1995, 1999 and 2004 Carrera et al (1998). show that a shock to one country has a greater impact on the other in the 1990s than in the 1980s.5 SeePotash (1969) and Rouquie (1978).…”
mentioning
confidence: 99%
“…Uma maneira mais simples de estimar a simetria dos ciclos de negócios, também encontrada na literatura foi feita por Uma outra metodologia utilizada nesta literatura pode ser encontrada em Carrera et al [1998].…”
Section: A Correlação Dos Choquesunclassified